Description of the female, pupa, and larva of Culex (Melanoconion) bahiensis Duret, and redescription of the male (Diptera: Culicidae) - Lestani, Eduardo A.; Rossi, Gustavo C. (Zootaxa, 2012)
We describe for the first time the female, pupa, and larva of Culex (Melanoconion) bahiensis and also redescribe the male and illustrate the male genitalia and the pupa and larva. This is the first record of the species for Argentina.